Project: Declassified + 24 season drums - Leow, Puay Tin *; Teh, Mark *; Azmyl Yunor, * (Sunway University. Dept. of Performance & Media, 2010)
PROJECT: DeClassified is a devised performance created by the March 2009 intake. It is based on classified ads in The Star of 26 January 2010. Contents: Myvi, Yourvi, Ourvi.- Lonely heart. - Who needs notes. - Spin. - Trust me. - The Gift. - Really got river. - Yes, Ma'am!. - Pasaraya hero.